2012
DOI: 10.1158/1078-0432.ccr-11-2852
|View full text |Cite
|
Sign up to set email alerts
|

A Phase I Clinical Trial of Ad5.SSTR/TK.RGD, a Novel Infectivity-Enhanced Bicistronic Adenovirus, in Patients with Recurrent Gynecologic Cancer

Abstract: Purpose Ad5.SSTR/TK.RGD is an infectivity-enhanced adenovirus expressing a therapeutic thymidine kinase suicide gene and a somatostatin receptor that allows for noninvasive gene transfer imaging. The purpose of this study was to identify the MTD, toxicities, clinical efficacy and biologic effects of Ad5.SSTR/TK.RGD in patients with recurrent gynecologic cancer. Experimental Design Eligible patients were treated intraperitoneally (IP) for 3 days with 1×109 to 1×1012 vp/dose of Ad5.SSTR/TK.RGD followed by intr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 36 publications
1
46
0
Order By: Relevance
“…In a phase 1 trial on hepatocellular carcinoma (NCT00844623) five consecutive cohorts of two patients received increasing doses of an HSV-TK suicide gene-encoding adenoviral vector by intratumoral injection; subsequently, equal doses of either intravenous ganciclovir (GCV) or oral vGCV were applied; no specific information on dosages or duration of prodrug therapies were provided. In a further phase 1 study on ovarian cancer (NCT00964756) patients were treated intraperitoneally for 3 days with an HSV-TK suicide geneencoding adenoviral vector followed by intravenous application of GCV (5 mg/kg twice daily; at a constant rate for more than 1 hour) for 14 days (Kim et al, 2012). In another phase 1 study in patients with head and neck cancer and other malignant tumors, single intratumoral injections of an adenoviral vector encoding HSV-TK were performed on day 1 followed by systemic (intravenous) administration of GCV (50 mg/kg twice daily) from days 2 to 15 (Xu et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In a phase 1 trial on hepatocellular carcinoma (NCT00844623) five consecutive cohorts of two patients received increasing doses of an HSV-TK suicide gene-encoding adenoviral vector by intratumoral injection; subsequently, equal doses of either intravenous ganciclovir (GCV) or oral vGCV were applied; no specific information on dosages or duration of prodrug therapies were provided. In a further phase 1 study on ovarian cancer (NCT00964756) patients were treated intraperitoneally for 3 days with an HSV-TK suicide geneencoding adenoviral vector followed by intravenous application of GCV (5 mg/kg twice daily; at a constant rate for more than 1 hour) for 14 days (Kim et al, 2012). In another phase 1 study in patients with head and neck cancer and other malignant tumors, single intratumoral injections of an adenoviral vector encoding HSV-TK were performed on day 1 followed by systemic (intravenous) administration of GCV (50 mg/kg twice daily) from days 2 to 15 (Xu et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The pros and cons of these molecules is beyond the scope of this review and the reader is invited to refer to the most updated review paper by Verheije and Rottier [80]. In a recent phase I clinical study by Kim et al (2012), the application of this technique has been demonstrated by using a tropism modified adenovirus carrying RGD sequence in the fiber knob[81]. As a result, the transfection of adenovirus depended on integrin receptors rather than CAR.…”
Section: Enzyme/prodrug Systems: From Bench To Bedmentioning
confidence: 99%
“…Currently, numerous OLVs, including adenovirus [1][2][3], reovirus [4], measles virus [5], Newcastle disease virus [6], Seneca Valley virus [7], retrovirus [8], vaccinia virus [9], herpes simplex virus [10] and Coxsackie virus A21 [10] are in or have completed clinical trials for a variety of solid malignancies with encouraging results.…”
Section: Introductionmentioning
confidence: 99%